A stratified study of students' understanding of basic optics concepts in different contexts using two-tier multiple-choice items - Chu, Hye-Eun; Treagust, David F.; Chandrasegaran, A.L. (Research in science & technological education, 2009)
A large scale study involving 1786 year 7-10 Korean students from three school districts in Seoul was undertaken to evaluate their understanding of basic optics concepts using a two-tier multiple-choice diagnostic instrument consisting of four pairs of items, each of which evaluated the same concept in two different contexts. The instrument, which proved to be reliable, helped identify several context-dependent alternative conceptions that were held by about 25% of students. At the same time, students' performance on the diagnostic test correlated with the location of the schools, students' achievement in school science and their attitudes to science learning. However, students' grade levels had limited influence on their understanding of basic concepts in optics as measured by the instrument.